A Multirate Approach for Fluid-Structure Interaction Computation with Decoupled Methods (Communications in Computational Physics, 2020)
We investigate a multirate time step approach applied to decoupled methods in fluid and structure interaction (FSI) computation, where two different time stepsare employed for fluid and structure respectively. For illustration, the multirate technique is examined by applying the decoupled $β$ scheme. Numerical experiments showthat the proposed approach is stable and retains the same order of accuracy as the original single time step scheme, while with much less computational expense.
Keywords: Fluid and structure interaction (FSI); decoupled methods; multirate time step; stability; β scheme.